Victorian writing about risk : imagining a safe England in a dangerous world - Freedgood, Elaine (Cambridge studies in nineteenth-century literature and culture, 2000)
"In Victorian Writing about Risk, Elaine Freedgood explores the geography of risk produced by a wide spectrum of once-popular literature, including works on politic economy, sanitary reform, balloon flight, Alpine mountaineering and African exploration. The consolations offered by this geography of risk are precariously predicated on the stability of dominant Victorian definitions of people and places. Women, men, the laboring and middle classes, the English and the Irish, Africa and Africans: all have assigned identities that allow risk to be located and contained. When identities shift and boundaries fail, danger and safety begin to appear in all the wrong places. The texts that this study focuses on reveal the ways in which risk moralizes and naturalizes the economic and political institutions of industrial, imperial culture during a period of unprecedented expansion and change."--Jacket